ANALISIS PERILAKU KONSUMTIF PENGGUNA SHOPEE PAYLATER DI DKI JAKARTA - Siti Aminah (2022)
This study examines the influence of conformity, lifestyle and self-control on consumptive behavior of Shopee PayLater users in DKI Jakarta Region. The non probability sampling technique with purposive sampling was used in this study by distributing questionnaires in the form of Google forms to social media and a sample of 100 respondents was taken. The data is then processed using the SmartPLS 4.0 application and the results state that conformity has a positive and significant influence on consumptive behavior of 0.239. Lifestyle has a positive and significant influence on consumptive behavior of 0.387. And self-control has a positive and significant influence on consumptive behavior of 0.358